The Poetic Universe of Mast Tawakli: In the Context of a Poem - Mehr, Rahim Bakhsh; Baloch, Zia Ur Rehman; Raziq, Abdul (sourcecoder, 2025)
Mast Tawakli is widely regarded as a prominent figure in Balochi classical poetry, celebrated for his unique contributions to the literary tradition. While many poets of his era composed poetry influenced by Persian and Arabic, Mast Tawakli stood apart for his distinctive style and his dedication to expressing himself in pure Balochi language. His poetry reflects a deep connection to his cultural roots, enriched by similes and metaphors crafted from his keen observations of the world around him. As a naturalist poet, Mast Tawakli found profound inspiration in nature, which he eloquently described through his verses, capturing its essence with remarkable precision. This research article explores Mast Tawakli’s poetry through the lens of environmental criticism, shedding light on his portrayal of the natural world and its intricate relationship with human existence. For this purpose, one of his poems has been carefully selected and analyzed to highlight how he observed and depicted the universe in exquisite detail. His vivid imagery and environmental themes resonate deeply with modern critical perspectives, offering a timeless appreciation of the natural world. Through this examination, Mast Tawakli emerges not only as a master of poetic diction but also as a visionary who celebrated the beauty and complexity of the environment through his art.